Partnership Working in Health and Social Care - Glasby, Jon.; Dickinson, Helen; Community Care (Organization : Great Britain) (Bristol : Policy, 2008)
Short, accessible and designed for everyday use, this is a 'warts and all' introduction to partnership working. It summarizes current policy and research, setting out frameworks and approaches, and helping policy makers and practitioners to work more effectively together.
Published in association with Community Care.
Includes bibliographical references (p. 93-101) and index.
Keywords: Public health -- Great Britain; Public welfare -- Great Britain; Medical policy -- Great Britain; Interagency coordination -- Great Britain; Society; Great Britain -- Social policy